Implementasi Linear Programming Dalam Mengoptimalkan Produksi Karet Olahan : Studi Pada Koperasi Produksi Perkebunan Karet Wangunwatie - Muhammad Haris Fadhillah (Universitas Koperasi Indonesia, 2022)
KPPKW latex productivity in 2013 – 2016 at KPPKW decreased by 13.48% which resulted in KPPKW not being able to produce processed rubber optimally, causing production costs and income to be not optimal. The purpose of this study was to test the optimum model of processed rubber at KPPKW. The method used in this research is a case study method with the help of linear programming using LINDO 6.1 software. The results showed that the optimal production cost was Rp 219,262,253 and the optimal profit was Rp 2,030,588.00 with an efficiency of 3.57% with a combination of RSS production of 135,292 kg and non-RSS of 6,000 kg. Analysis of resource status shows that the constraint that is limiting the production of processed rubber in KKPKW are auxiliary materials and non-RSS production estimates. With this research, it is hoped that it can be applied to cooperatives for optimal rubber planning in the future.